PENGARUH CARA PENYEMAIAN DAN PEMUPUKAN NPK TERHADAP PERTUMBUHAN BIBIT MAHONI DAUN LEBAR DI PESEMAIAN - Hamdan Adma Adinugraha (Jurnal Pemuliaan Tanaman Hutan, 2012)
Swietenia macrophylla King is one of popular tree species for timber product in Java. In order to increase the productivity of planting stock production at nursery, this research was conducted. The objectives of this research was to study the influences of sowing method and NPK fertilizer application on the growth of mahogany seedlings at nursery. The treatments were sowing methods (with and without pricking out), types of NPK fertilizer (grain and solution) and the dosages of NPK fertilizer (0, 0.2, 0.4 and 0.6 gram/seedlings). The result showed that sowing methods and type of NPK fertilizer did not give significant effect on the growth of mahogany seedlings. The dosages of NPK fertilizer caused significant different on the variation of height, diameter, total dry weight and seedling quality index. The application of NPK fertilizer at 0.6 g/seedlings/month showed the best result i.e: the seedling heigth (42 cm), stem diameter (5.15 mm), total dry weight (5.28 g) and seedling quality index (0.38).